Fortalecimiento de capacidades ambientales a los socios de los centros poblados de Ricardo Palma y Bagazán para la creación de concesiones para la conservación Pachiza - Rengifo Ortiz, Laura Elena (2015)
localities aimed for such implementation of thesis project are the Ricardo Palma and Bagazan populated centers, located in the Pachiza District, Mariscal Caceres ProvinceSan Martin, with an emphasis to form an association and strengthen the capacities and environmental expertise of the partners in each association of each village center for the creation of conservation areas Shitariyacu y Tres Quebradas respectively. To meet with the thesis project established, was carried out in the first place the recognition of both population centers, the presentation befare the settlers with the purpose to inform the present draft of the thesis and presentation of the schedule and the tapies for the training, prior to the commencement of the environmental capacity building was conducted a survey of open ended questions with the goal of forming an association; in second place was in the initial evaluation and diagnosis of the basic knowledge to the partners of the towns of Ricardo Palma y Bagazan in tapies of (association, conservation area, wild flora, wildlife, water, soil, air, forests, biodiversity, etc. ), as the third point began strengthening the environmental skills to the creation of a conservation area to the partners in the above-mentioned items with their respective sub-themes; and the fourth and final evaluation and analysis of the final survey of the knowledge acquired with the training and strengthening, concluding this way in the development of the dustmen ecological facts to base of recycled plastic bottles and wires, in each association.